The synthetic character of Francisco Suarez's philosophy - Kucharczyk, Janusz (Folia Philosophica, 2001)
Francisco Suarez’s (1548-1617) philosophy remains as it were in the background among various philosophical systems which have emerged in history. It seems to be deeply rooted in scholasticism and it was for this reason suspected of being anachronic. On the other hand it was also suspected of departure from St. Thomas Aquinas ideas of a distortion of his thought. In its essence, however, this thought is a synthesis of different currents in scholasticism (Tomism, Scottism, nominalism) and though it principally does not go beyond the limits of this kind of practicing philosophy, within those limits it is new and different enough as to significantly influence the emergence of 17lh-century thought. This thought owes its originality first of all to its synthetic character. Themes taken from different Medieval philosophical traditions constitute a new quality. Suarez unexpectedly puts together genetically different elements so that it seems on the one hand to reject them all without accepting any of the solutions proposed by them in their pure form, while on the other he preserves them though creating a qualitatively new thought. He takes such a position in the traditional disputes taken within the oppositions: monism/dualism/pluralism, nominalism/realism or in the controversy concerning the nature of matter. In fact, despite the declared faithfulness to tradition (especially the Tomist tradition) he does not accept any of the traditional solutions bringing in new proposal which are neutral in the face of the existing ones. The synthetic character of this philosophy universal enough to be also expressible in the language of the basic traditions of the antique philosophy so that what can be perceived in his conception is an attempt at reconciling Parmenideism, Platonism, Arstotelism and Stoicism as well.